IIIT Intellectual Panels at the ISNA 50th Annual Convention (American Journal of Islam and Society, 2014)
The International Institute of Islamic Thought (IIIT) organized a two-day seriesof intellectual panels at the Islamic Society of North America’s (ISNA) 50thannual convention, held in Washington, DC, over the Labor Day weekend(Aug. 31–Sept. 1, 2103). These events were hosted in the institute’s hospitalitysuite on the main floor of the Washington Convention Center. Recently publishedIIIT books and other selected publications were prominently displayed.A documentary on IIIT and its goals was shown before each session.